ANALISIS KEMAMPUAN PEMAHAMAN KONSEP PERSAMAAN DAN PERTIDAKSAMAAN NILAI MUTLAK PADA PESERTA DIDIK KELAS X IPS SMAN 13 PADANG: KEMAMPUAN PEMAHAMAN KONSEP PERSAMAAN DAN PERTIDAKSAMAAN NILAI MUTLAK - Yeli Andani; Rita Desfitri (Jurnal Tunas Pendidikan, 2023)
ABSTRACT This study aims to describe and analyze the ability to understand the concept of absolute value equations and inequalities in class X IPS students at SMAN 13 Padang. Analyze students' conceptual understanding abilities in this study, can be seen from four indicators, namely: (1) rewriting a concept; (2) presenting concepts in the form of mathematical representations; (3) using, utilizing, and selecting certain procedures or operations; (4) apply concepts or algorithms in problem-solving. The question in this study is how is the ability to understand the concept of absolute value equality and inequality in class X IPS students at SMAN 13 Padang. The method in this research is a qualitative method with a descriptive research type. The subjects in this study were 33 class X IPS 1 students at SMAN 13 Padang who were selected by purposive sampling. From the results of the research conducted, the ability to understand students' mathematical concepts as an indicator of the ability to understand mathematical concepts, especially in rewriting a concept and presenting concepts in the form of mathematical representations, is very good. On indicators of the ability to understand concepts in using, utilizing, and selecting certain procedures or operations and applying algorithms in problem-solving with the sufficient category. From the research results obtained, it is suggested that teachers can provide exercises to improve students' ability to understand mathematical concepts. Keywords : Analysis, Level of Ability, Concept Understanding